Analisa Dan Perancangan Pelayanan Pada Rumah Sakit Berbasis Web - Herasmus, Hilda (Riset Sinergi Indonesia (RISINDO), 2022)
In today's sophisticated era, hospitals are required to increase their performance and competitiveness without reducing their social mission. Hospitals must determine strategic ideas, including being able to quickly and accurately make decisions to improve services to the community. Hospital Service Information Systems are computerized systems that process and integrate all health service business process flows in the form of coordination networks, reporting and administrative procedures. to support performance and obtain information quickly, precisely and accurately. A computer-based Management Information System is a very important supporting tool, one might even say absolute, for hospital operations. Various experiences of hospitals using conventional administrative systems show that there are many lost opportunities to gain profits due to weak coordination between departments and a lack of fast, precise, accurate and integrated information support.